The Role of Digital Transformation through Modular ERP in Enhancing Corporate Adaptability to Global Market Changes - Irnawati, Irnawati; Rahayu, Rahayu (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study explores the role of digital transformation through modular ERP systems in enhancing corporate adaptability to global market changes. In today’s rapidly evolving business environment, organizations need flexible and scalable solutions to remain competitive. The research examines how modular ERP systems, which allow customization and scalability, help organizations navigate dynamic global market shifts. Using a qualitative research design, data were collected through semi-structured interviews with key stakeholders from 10 organizations across various sectors, including manufacturing and retail. Thematic analysis was applied to the data to identify key patterns in how ERP systems support business adaptability, decision-making, and operational efficiency. The findings reveal that modular ERP systems significantly improve adaptability by enhancing business processes, enabling real-time decision-making, and facilitating market responsiveness. Companies reported increased scalability and efficiency in responding to market changes, particularly in areas such as supply chain management and financial reporting. Despite these benefits, challenges such as high implementation costs and complex customization were identified as barriers to adoption. The study contributes to the existing literature on digital transformation by highlighting the strategic advantages of modular ERP systems beyond automation, specifically in improving organizational flexibility and market responsiveness. The findings offer practical insights for businesses seeking to leverage ERP systems to stay competitive in an unpredictable global market. Future research should focus on exploring the long-term impacts of ERP systems and addressing the barriers to their full implementation.